Development of REACT-Based E-Module to Improve Students' Scientific Literacy Ability in Buffer Solution - Karmila, Aroma; Kurniawati, Desy; Hardeli, Hardeli; Nizar, Umar Kalmar (FKIP Universitas Lampung, 2022)
The buffer solution e-module based on the REACT strategy (Relating, Experiencing, Applying, Collaborating, Transferring) has been developed and analysed for its validity and practicality levels to assist the learning process of students to train students' scientific literacy skills. This research belongs to the type of EDR (Educational Design). Research) with the Plomp model. The research tools used were interview forms, validity questionnaires, and practicality. This e-module has been verified by six expert reviews, and 9 students became research subjects in this development research. Data were analysed using Aikens'V formula, and practicality percentage. Analysis of the validity of the questionnaire data showed an Aikens' V average score of 0.89 (for construct validity). Analysis of the practicality questionnaire data showed an average score of 83% and 83% (for small groups and field practice tests). Data analysis shows that the e-module has a high level of validity and practicality. Therefore, it can be concluded that the buffer solution e-module teaching material based on the REACT strategy is valid and practical so that it is feasible to use it in learning to train students' scientific literacy skills. Keywords: e-module, REACT strategy, buffer solution, scientific literacy DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp866-879